UNO PEACE-SUPPORT MISSION IN DONDAS: MYTH OR REALITY? - Зельманович, І. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyses the peculiarities of the activities of the United Nations, as well as the question of the possible international peacekeeping effort of the UNO in occupied Donbas. All the advantages, as well as risks that Ukraine may encounter when considering this issue have been analysed. The article focuses on the mandate and the numerical strength of the mission. It is noted that the Ukrainian state should make every effort to ensure that the international peacekeeping contingent becomes one of the effective parts that will contribute to the restoration of Ukraine's sovereignty and territorial integrity.